Spatio-Temporal Variation in the Phyllospheric Microbial Biodiversity of Alternaria Alternata-Infected Tobacco Foliage - Dai, Yuan-feng; Wu, Xiao-mao; Wang, Han-cheng; Li, Wen-hong; Cai, Liu-ti; Li, Ji-xin; Wang, Feng; Sehar, Shafaque; Shamsi, Imran Haider (Frontiers in Microbiology, 2022)
Phyllospheric microbial composition of tobacco (Nicotiana tabacum L.) is contingent upon certain factors, such as the growth stage of plant, leaf position and cultivar as well as its geographical location, which influence, either directly or indirectly, the growth, overall health and production of tobacco plant. To better understand the spatiotemporal variation of the community and divergence of phyllospheric microflora, procured from healthy and diseased tobacco leaves infected by Alternaria alternata, the current study employed microbe culturing, high-throughput technique and BIOLOG ECO. Microbe culturing resulted in the isolation of 153 culturable fungal isolates belonging to 33 genera and 99 bacterial isolates belonging to 15 genera. High-throughput sequencing revealed that the tobacco’s phyllosphere was dominantly colonized by Ascomycota and Proteobacteria whereas, the most abundant fungal and bacterial genera were Alternaria and Pseudomonas. The relative abundance of Alternaria increased in upper and middle healthy groups from the first collection time to the third; whereas, the relative abundance of Pseudomonas, Sphingomonas and Methylobacterium from the same positions increased during gradual leaf aging. Non-Metric Multi-Dimensional Scaling showed clustering of fungal communities in healthy samples, while bacterial communities of all diseased and healthy groups were found scattered. FUNGuild analysis, from the first collection stage to the third one in both groups, indicated an increase in the relative abundance of Pathotroph-Saprotroph, Pathotroph-Saprotroph-Symbiotroph and Pathotroph-Symbiotroph. Inclusive of all samples, as per the PICRUSt analysis, the predominant pathway was metabolism function accounting for 50.03%. The OmniLog Units average values showed relatively higher utilization rates of carbon source by the microbial flora of healthy leaves. According to the analysis of genus abundances, leaf growth and leaf position were the important drivers of change in structuring microbial communities. The current findings revealed the complex ecological dynamics that occur in phyllospheric microbial communities over the course of a spatiotemporal varying environment with the development of tobacco brown spot, highlighting the importance of community succession.